Relationship between technology acceptance towards attitude of work performance at Universiti Tun Hussein Onn Malaysia (UTHM) / Noor Hashimah Hisamudin - Hisamudin, Noor Hashimah (2015)
The purpose of this study is to examine the relationship between technology acceptance toward attitude of work performance. The employees' acceptance was measured through two main variables which is technology acceptance and work performance. The element of technology acceptance are perceived ease of use, user interface, and social influence. Whereby, the element of work performance is attitude. The respondents for this study were 80 employees at Universiti Tun Hussein Onn Malaysia (UTHM). In order to perform the statistical analysis, Statistical Packages for the Social Science (SPSS) version 20.0 was used. All 80 questionnaires distributed were returned. The research question and hypothesis have been tested. The findings concluded that there is a relationship between both technology acceptance and work performance. For recommendations, the researcher suggested to widen the methods of data subjects. Besides that, the researcher also suggested to increase the number of respondents, to generalize the findings. Moreover, the researcher also further suggested that the research would look at a wider scope on the technology acceptance.